Behaviour of a PVD unit cell under vacuum pressure and a new method for consolidation analysis. (April 2020) - Chai, Jin-chun; Fu, Hong-tao; Wang, Jun; Shen, Shui-Long
Abstract: The behaviour of a prefabricated vertical drain (PVD) unit cell with clays of high initial water content has been investigated by laboratory model tests and finite element analysis (FEA). The results indicate that there is considerable horizontal soil movement towards the PVD. The soils in the zone near the PVD are in horizontal compression, and the other zones are in horizontal tension. The surface settlements are not uniform, and the soil at the periphery of the unit cell settles more than the soil near the PVD. The model test results indicate that the phenomenon of soil particle separation does not occur, and it implies that the main mechanism of apparent "clogging" is due to non-uniform consolidation. The results of the FEA indicate that at the end of vacuum consolidation, the soil adjacent to the PVD has a higher effective vertical stress as well as undrained shear strength, but the stress state is very close to the critical state line. Then, a new explicit consolidation analysis method has been established/verified for considering the variations of consolidation properties, including apparent clogging during the consolidation process.